A systematic revision of Charissa, subgenus Pterygnophos Wehrli, 1951, with description of a new species (Lepidoptera: Geometridae) - Erlacher, Sven; Palma, Laura Marrero; Erlacher, Josepha (Zootaxa, 2017)
The subgenus Pterygnophos Wehrli, 1951 within the genus Charissa Curtis, 1826 nomen protectum (= Hyposcotis Hübner, [1825] nomen oblitum) is taxonomically revised based on morphology and DNA barcoding. The subgenus comprises four species in total which are presented in detail. Diagnostic characters are depicted and keys to the species based on the morphology of male and female genitalia are provided. Males and females of each species and their genitalia are illustrated. The distribution of all species is described and figured on a map, and a neighbor joining tree based on DNA barcoding of 17 specimens is presented. Charissa (Pterygnophos) beljaevi spec. nov. from Mongolia is described as new. A neotype for Gnophos creperaria Erschoff, 1877, and lectotypes for Gnophos deliciaria shantungensis Wehrli, 1953, Gnophos dorkadiaria Wehrli, 1922, Gnophos ochrofasciata Staudinger, 1895, and Gnophos finitimaria Fuchs, 1899 are designated. The following synonyms are recognized: Gnophos finitimaria Fuchs, 1899 syn. nov. is a synonym of Gnophos ochrofasciata Staudinger, 1895 and Gnophos deliciaria shantungensis Wehrli, 1953 syn. nov. is a synonym of Gnophos agnitaria Staudinger, 1897.